![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) x + 45 -[ 90 + (-20) + 5 - (-45)] +3x
= x +45 -( 90 - 20 + 5 + 45) + 3x
= x +45 -120 +3x
= -75 +4x
b) x +(-294 +13 -2x) +(94 -13) +9x
= x -281 -2x +81 +9x
= -200 +8x
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
(x – 2) – (39 – 45) = | - 5| - | -10|
(x - 2) - 6 = 5 - 10
(x - 2) - 6 = - 5
x - 2 = - 5 + 6
x - 2 = 1
x = 1 + 2
x = 3
Vậy x = 3
\(\left(x-2\right)+6=-5\)
\(\Rightarrow x-2=-11\)
\(\Rightarrow x=-9\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(5\left(7+48:x\right)=45\)
\(\Leftrightarrow\left(7+48x\right)=9\)
\(\Leftrightarrow4x=2\)
\(\Leftrightarrow x=2\)
________________
\(5^2x-3.2.5^2=5^2.3\)
\(\Leftrightarrow5x^2-3-2.5^2=75\)
\(\Leftrightarrow5x^2-3-50=75\)
\(\Leftrightarrow5x^2-3=125\)
\(\Leftrightarrow5x^2=128\)
\(\Leftrightarrow x^2=\frac{128}{5}\)
\(\Leftrightarrow\orbr{\begin{cases}x=\frac{128}{5}\\x=-\frac{128}{5}\end{cases}}\)
___________________
\(2+x:5=0\)
\(\Leftrightarrow x:5=-2\)
\(\Leftrightarrow x=-10\)
\(10+2x=16\)
\(\Leftrightarrow2x=6\)
\(\Leftrightarrow x=3\)
![](https://rs.olm.vn/images/avt/0.png?1311)
45 - 9 x ( 13 + 5 )
= 9 x 5 - 9 x 13 + 9 x 5
= 9 x ( 5 - 13 + 5 )
= 9 x ( -3 )
= -27
k hộ mình nhà
![](https://rs.olm.vn/images/avt/0.png?1311)
a/ => 2x - 4 = 22 = 4
=> 2x = 8
=> x = 4
b/ => 60 : 2x = 10
=> 2x = 6
=> x = 3
c/ => 5(2x - 3) = 25
=> 2x - 3 = 5
=> 2x = 8
=> x = 4
d/ => 3x - 6 = 34 : 3 = 33 = 27
=> 3x = 33
=> x = 11
![](https://rs.olm.vn/images/avt/0.png?1311)
a, 45 - 45 . ( -12 + 3 )
= 45 - 45 . (-9)
= 45 -(- 405)
=450
b, 31 . ( -18 ) + 31 . ( - 81 ) - 31
= 31. [ -18 + (-81 ) - 1 ]
= 31. (-100)
= -3100
![](https://rs.olm.vn/images/avt/0.png?1311)
-45 : 5 . ( -3 - 2x ) = 3
5 . ( -3 - 2x ) = ( -45 ) : 3
5 . ( -3 - 2x ) = -15
-3 - 2x = ( -15 ) : 5
-3 - 2x = -3
2x = ( - 3 ) - ( -3 )
2x = 0
x = 0 : 2
x = 0
=> 5.(-3-2x) = -45 : 3 = -15
=> -3-2x = -15 : 5 = -3
=> 2x = -3 - (-3) = 0
=> x = 0 : 2 = 0
Vậy x = 0
Tk mk nha
2x+5= - 45
2x = - 45-5
2x = - 50
x = - 50 : 2
x =- 25